The Study of Hokkien with a Comparison of the Current Hokkien Situation in Taiwan and the Philippines - Zixin Chen (Studies in Social Science & Humanities, 2023)
This study draws on the history of Hokkien and introduces the spreading of Hokkien worldwide. The current situation of Hokkien educational delivery at the family level, school level, and government level in Taiwan and the Philippines is stated. Comparing education service delivery in Taiwan and the Philippines, the author gives recommendations on the preservation of Hokkien in Taiwan on the three levels mentioned above.